Nghiên cứu tác động của rủi ro chính sách kinh tế toàn cầu đến đầu tư của doanh nghiệp trên sàn chứng khoán Việt Nam - Võ Xuân, Hồng; Nguyễn Cảnh, Tiên (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
The paper investigates the effect of global economic policy uncertainty (GEPU) on investment by publicly listed firms in Vietnam, based on a sample of 602 firms listed on Ho Chi Minh City Stock Exchange (HoSE) and Hanoi Stock Exchange (HNX) for the period 2011–2021. The authors find that firms reduce investment during high GEPU periods. The negative effect of GEPU on investment is significantly stronger in firms that are more dependent on external financing, more financially constrained, have a higher degree of investment irreversibility, or possess higher market power. These findings have important implications for the Vietnamese government in revising policies and resolutions, especially those related to financing, to support firms during periods of high GEPU.
Keywords: Economic policy uncertainty; Investment; Vietnam